Protecting State Border: Risk and Prevention. Economic Dimension - Aiva Zuzevičiūtė; Saulius Greičius; Darius Valkavičius; Danguolė Seniutienė (Montenegrin Journal of Economics, 2017)
This paper aims at discussing to what extent an effective protection of a state border (in this case: the external EU border that partly coincides with the border of the Republic of Lithuania, which amounts to 1070 km. (the whole perimeter of a border amounts to 1763 km)) depends on successful prevention and dismantling of activities of trafficking networks and on understanding the economic mechanisms for the operation of those networks. The paper will introduce the pilot study (completed in Spring, 2017) with an aim to identify the concepts officers – state border guards have on diversity and migration; first chapter is dedicated to the issue. Also, an analysis of the Lithuanian situation is presented in the second chapter. The fact that during the last several years (since 2012), the number of irregular migrants decreased by almost 4 times is discussed from two aspects. Firstly, measures of prevention and infrastructure. Namely, the distance under the surveillance of CCTV cameras increased twofold during the time, also, the cooperation with colleagues in the field in other countries (Byelorussia) improved significantly. Another factor was an improved cooperation of the law enforcement agencies between the countries and within Lithuania. The data shows that one of the major factors for decreasing the illegal migration that is, prevention is a successful removal of economic factor from the process (or at least, it serves as a strong deterrence). That is, it was identified that the predominant number of irregular migrants were doing that not as individuals, but in the groups, led by traffickers, whose fee in recent years increased. Therefore, effective legal measures against traffickers provide solid basis for decreasing irregular migration.